A Historical Review of the Technology Used for the Study of Freshness in Red Meats - Julieta Nava-Granados; Maria T. Orvananos-Guerrero; Claudia N. Sanchez; Julieta Dominguez-Soberanes (IEEE Access)
Meat is a high-quality source of protein, vitamins, and minerals, making it a fundamental component of the human diet. Ensuring the availability of fresh meat is, therefore, essential for both consumers and the food industry. Traditional methods for assessing meat freshness, such as sensory evaluation and chemical analysis, are often manual, time-consuming, costly, and may lead to human interpretation errors. In contrast, advanced non-destructive technologies—supported by data-driven analysis—offer efficient, accurate, and objective alternatives. This review provides a comprehensive historical overview of the methods used to assess red meat freshness, including their advantages, limitations, and applications. Furthermore, it discusses state of the art data analysis techniques to enhance detection accuracy, highlighting the potential for industrial implementation and the challenges that must be addressed.